Prospective analysis of principles and frequency of self-adjustment of insulin dose in people with diabetes type 1 before and after participation in a diabetes treatment and teaching programme. (September 2016) - Kramer, Guido; Kuniss, Nadine; Jörgens, Viktor; Lehmann, Thomas; Müller, Nicolle; Lorkowski, Stefan; Wolf, Gunter; Müller, Ulrich A.; Kloos, Christof
Highlights: There is no data available how patients adjust their insulin under "real life" conditions on a long run. All patients adjusted their insulin after participation in these education programmes. 72.8% of the patients used adjustment rules which were trained beforehand. The number of patients using bolus calculators increased after participation in the programme substantially. Abstract: Objective: Insulin dose self-adjustment is an essential part of intensified insulin therapy – nowadays the routine treatment of type 1 diabetes (DM1). The aim of this study was to evaluate principles and frequency of insulin dose self-adjustments in people with DM1 before and one year after participating in a structured diabetes treatment and teaching programme (DTTP) and to determine to which extent the patients followed the way they had been trained. Methods: 72 people with DM1 were interviewed before participation in our inpatient (32/72) or outpatient (40/72) DTTP. Sixty-six participants (91.7%) were followed up after one year. The number of adaptations of the insulin dose by the patients was recorded from 28 days of the patients' diary. The ability to find the correct dose was tested using five different examples. Results: Metabolic control improved significantly after one year (7.9 ± 1.0 to 7.5 ± 0.8%, p = 0.004). The participants performed 86.0 ± 37.1 insulin dosage adaptations per 28 days before the DTTP. After one year the frequency increased significantly to 99.1 ± 30.7 per 28 days ( p = 0.011). Before the DTTP, 42 of 72 patients (58.3%) adjusted their insulin dose to correct high blood glucose levels by adjustment rules (factor for correction or correction scheme) and 20 of 72 people (27.8%) by personal experience/feeling. One year after the DTTP, 73% (48/66) used adjustment rules. Conclusions: After participating in an structured education programme, patients adjusted their insulin dosage more frequently. Metabolic control improved despite the fact that many patients did not strictly apply the rules they had been trained for.